Physiological quality of canola seeds under different sowing and harvesting times - Panozzo, Luís Eduardo; Silva, Fred Denilson Barbosa da; Pinto, Luciana Barros; Dias, Denise Cunha Fernandes dos Santos; Dörr, Caio Sippel; Magano, Deivid Araújo; Spinelli, Victor Mouzinho; Maia, Luciano Carlos da; Silva, José Antônio Gonzalez da; Stefanello, Giusepe (Australian journal of crop science, 2025)
To expand and implement the cultivation of canola in an agricultural production system, it is essential for the production and use of high-quality seeds. The objective of this research is to evaluate the germination of hybrid seed during different sowing and harvesting dates. The experiment was conducted at the experimental site and the Seed Laboratory of Federal University of Viçosa. The hybrids canola Hyola 432, 433, 401 and 61 were sown and harvest in different dates. After the seed processing, the seeds were evaluated for germination, first count of germination, speed of germination, time, and average velocity of germination. The experimental design was a randomized complete block 4 hybrids x 4 sowing times x 3 harvest times and with four replications. Data from qualitative factors were submitted to variance analysis and compared by Tukey’s test and quantitatively factors were compared by regression analysis. To harvest seeds with high physiological quality it is necessary to sow between May and June and harvest after reaching physiological maturity until a maximum of 10 days. The seeds of Hyola 401 showed better seed quality, based on the results of all the variables studied, regardless of sowing and harvesting date.